The effect of 10 weeks of karate training on the development of motor skills in children who are new to karate - Arslan, Yasin; Yavaşoğlu, Belma; Beykumül, Ayşegül; Pekel, Aylin Özge; Suveren, Ceren; Karabulut, Ebru Olcay; Ayyıldız Durhan, Tebessüm; Çakır, Veli Ozan; Sarıakçalı, Nuriye; Küçük, Hamza; Ceylan, Levent (Frontiers in Physiology, 2024)
This study investigated the effect of a 10-week karate training program on the motor skill development of 5-7-year-old children new to karate with two different test batteries. A total of 28 participants were included in the study: 18 in the Karate group and 10 in the control group. The karate group was subjected to a fundamental karate training (kihon) program consisting of 90-minute sessions four days a week for ten weeks in addition to physical education classes at their schools. In contrast, the control group did not participate in any sportive activities except physical education classes in their schools. Data were collected using the Eurofit test battery and the TGMD-2 test. The Eurofit Test Battery, frequently preferred in young children, is mainly used to measure children's physical fitness. The motor development level of children directly affects physical fitness. For this reason, the Eurofit Test Battery can be used to observe the level of motor development through physical fitness. In the pre-post test comparison of the anthropometric measurements of the karate group, no significant difference was found in the control group. In contrast, a significant difference was obtained in height, body mass index, and body fat percentage. In the post-test analysis of the two independent groups, there were statistically significant differences in favor of the karate group regarding height and body fat percentage (p<0.005). In the pre-post analysis of the Eurofit test and the TGMD-2 for the karate group, all parameters showed statistically significant improvements (p < 0.001), while the control group showed no statistical difference. After comparing the karate and control groups, the Eurofit Test and TGMD-2 post-test results showed significantly higher scores (statistically significant differences) in all parameters for the karate group. In conclusion, the study shows that the 10-week karate training program positively affected the motor development of the participating children. Notably, both test batteries showed similar results, confirming the parallel nature of the results.